Dishonesty in science - Todorović, Slobodan; Toskovic, Borislav; Mrda, Davor; Gacic, Jasna; Todorovic, Tatjana (Halo 194 Scientific Journal of Emergency Medicine, 2020)
With the formation of the global network, various information became available to scientists. Scientists and the professional public must be sure that the research of their colleagues is true, objective, and the results of the research are complete. Scientific misconduct can occur in various forms and in all phases of the scientific research process. Usually it occurs in the form of fabrication, falsification and plagiarism. Reasons for scientific misconduct can be personal, professional and financial. A special area is the "gray zone" and it consists of data manipulation and selection, errors in quoting references, multiple and "salami" publications, and problematic authorship. The appearance of a violation of the scientific-research code diminishs the reputation of the scientific community, but it also misleads other researchers, which significantly slows down scientific development. Digitalization and technological advances contribute significantly to the rapid detection, elimination and sanctioning of any form of research misuse.
Keywords: scientific misconduct, fabrication, falsification, plagiarism